Semantics-Driven Migration of Java Programs: a Practical Experience - Artyom O. Aleksyuk; Vladimir M. Itsykson (Моделирование и анализ информационных систем, 2017)
The purpose of the study is to demonstrate the feasibility of automated code migration to a new set of programming libraries. Code migration is a common task in modern software projects. For example, it may arise when a project should be ported to a more secure or feature-rich library, a new platform or a new version of an already used library. The developed method and tool are based on the previously created by the authors a formalism for describing libraries semantics. The formalism specifies a library behaviour by using a system of extended finite state machines (EFSM). This paper outlines the metamodel designed to specify library descriptions and proposes an easy to use domainspecific language (DSL), which can be used to define models for particular libraries. The mentioned metamodel directly forms the code migration procedure. A process of migration is split into five steps, and each step is also described in the paper. The procedure uses an algorithm based on the breadth- first search extended for the needs of the migration task. Models and algorithms were implemented in the prototype of an automated code migration tool. The prototype was tested by both artificial code examples and a real-world open source project. The article describes the experiments performed, the difficulties that have arisen in the process of migration of test samples, and how they are solved in the proposed procedure. The results of experiments indicate that code migration can be successfully automated.